2000
DOI: 10.1177/000271620057000104
|View full text |Cite
|
Sign up to set email alerts
|

Globalization in Southeast Asia

Abstract: The authors attempt to accomplish four interrelated tasks in this article: (1) to develop a plausible and defensible approach to studying globalization; (2) to define Southeast Asia; (3) to delimit and historicize the globalization process in Southeast Asia; and (4) to describe and analyze the economic performance of Southeast Asia over the past 30 years or so, paying particular attention to the region before, during, and after the events of 1997.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Globalization is one of the most contentious phenomena and controversial ideas of our time (Weiss, ), especially due to its worldwide impacts and numerous actors and vested interests, as well as its massive studies and diverse approaches adopted in almost all fields of knowledge (Kim, ). Despite the immense diversity in the interpretations and intellectual sources of globalization (Farazmand, ; Coclanis and Doshi, ; Tillah, ), it can be commonly defined as “a process of integrating nations, societies, and peoples in the domains of economy, politics, culture, ideology and knowledge through the transnational networks of capital, production, exchange, technology, and information owned and controlled unequally by dominant states, organizations, classes, and individuals” (Haque, ).…”
Section: Globalization‐led Public Administration: An Analytical Framementioning
confidence: 99%
See 4 more Smart Citations
“…Globalization is one of the most contentious phenomena and controversial ideas of our time (Weiss, ), especially due to its worldwide impacts and numerous actors and vested interests, as well as its massive studies and diverse approaches adopted in almost all fields of knowledge (Kim, ). Despite the immense diversity in the interpretations and intellectual sources of globalization (Farazmand, ; Coclanis and Doshi, ; Tillah, ), it can be commonly defined as “a process of integrating nations, societies, and peoples in the domains of economy, politics, culture, ideology and knowledge through the transnational networks of capital, production, exchange, technology, and information owned and controlled unequally by dominant states, organizations, classes, and individuals” (Haque, ).…”
Section: Globalization‐led Public Administration: An Analytical Framementioning
confidence: 99%
“…The main actors involved in colonial territorial expansion in South and Southeast Asia were the trading companies and the incipient Western capitalist states as their main patrons. It is suggested that these European powers tried “to establish and enforce close economic, political, and cultural ties between themselves and their respective colonies or in some cases groups of colonies” (Coclanis and Doshi, :53).…”
Section: Globalization the State And Public Administration In Asiamentioning
confidence: 99%
See 3 more Smart Citations